Sufisme-Based Character Practices At Darul Afkar Islamic Boerding School Klaten - Wahyudi, M. Agus; Azhar, Azhar; Shadiqin, Sehat Ihsan (Jurnal Spiritual Healing, 2023)
Character education is a system of cultivating character values which includes components of knowledge, awareness or will, and actions to carry out values that are considered noble. Islamic boarding schools are one of the Islamic religious educational institutions that have a role in contributing to instilling character education values in their students or students. One of the studies carried out at Islamic boarding schools is the study of Sufism, namely the science that teaches how to have noble morals. The purpose of this study was to find out how the practice of internalizing character education at the Darul Afkar Klaten Islamic Boarding School which is based on Sufism. The results of the study show that the practice of reciting blessings, reciting zikir, and sufistic therapy has a correlation in inculcating character education. Keywords: Character Education, Sufism, Islamic Boarding Schools.